1998
DOI: 10.1161/01.atv.18.1.100
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Low Density Lipoproteins in Patients With Transplant-Associated Coronary Artery Disease

Abstract: Abstract-The monoclonal antibody 4E6 -based ELISA was used to quantify levels of oxidized LDL in plasma of 65 control subjects, 47 patients transplanted for dilated cardiomyopathy (DCM), and 60 patients transplanted for coronary artery disease (CAD). Levels of oxidized LDL were 0.68Ϯ0.039 mg/dL (meanϮSEM), 1.27Ϯ0.14 mg/dL (PϽ.001 versus control), and 1.73Ϯ0.13 mg/dL (PϽ.001 versus control and Ͻ0.01 versus DCM), respectively. Levels of oxidized LDL were significantly lower in transplanted patients with angiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
99
0
6

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 163 publications
(111 citation statements)
references
References 38 publications
6
99
0
6
Order By: Relevance
“…First, oxLDL Ab may eliminate oxLDL particles from the circulation and prevent them from reentering the arterial wall. We 21 and others 34,35 have shown that oxLDL is detectable in human plasma at a very low concentration. We recently found that oxLDL Ab titer correlated inversely with plasma oxLDL concentration in a healthy population.…”
Section: Discussionmentioning
confidence: 62%
“…First, oxLDL Ab may eliminate oxLDL particles from the circulation and prevent them from reentering the arterial wall. We 21 and others 34,35 have shown that oxLDL is detectable in human plasma at a very low concentration. We recently found that oxLDL Ab titer correlated inversely with plasma oxLDL concentration in a healthy population.…”
Section: Discussionmentioning
confidence: 62%
“…42,44,45) Due to experimental differences, the actual values cannot be directly compared to each other. However, it is reasonable to believe that the various studies clearly indicate the involvement of oxidative modification of LDL in these clinical conditions.…”
Section: Oxldl and Various Diseasesmentioning
confidence: 99%
“…In retrospective studies, we have demonstrated an association between angiographically detected coronary artery disease (CAD) and plasma levels of oxidized LDL. 3,4 However, the retrospective data did not allow us to conclude whether the increase of plasma levels of oxidized LDL was a consequence of the development of CAD or whether oxidized LDL was an independent risk factor of transplant CAD. The aim of the present prospective study was to assess the prognostic value of oxidized LDL for CAD.…”
mentioning
confidence: 98%